RIG-I-Like Receptors as Novel Targets for Pan-Antivirals and Vaccine Adjuvants Against Emerging and Re-Emerging Viral Infections - Yong, Hui Yee; Luo, Dahai (Frontiers in Immunology, 2018)
Emerging and re-emerging viruses pose a significant public health challenge around the world, among which RNA viruses are the cause of many major outbreaks of infectious diseases. As one of the early line of defence in the human immune system, RIG-I-like receptors (RLRs) play an important role as sentinels to thwart the progression of virus infection. The activation of RLRs leads to an antiviral state in the host cells which triggers the adaptive arm of immunity and ultimately the clearance of viral infections. Hence, RLRs are promising targets for the development of pan-antivirals and vaccine adjuvants. Here, we discuss the opportunities and challenges of developing RLR agonists into antiviral therapy and vaccine adjuvants against a broad range of viruses.